(3GdQVG Yf Gddg hGdUHQ Ydi bVGFg hGdJSdje dCeQgs - (3YHO Gddg Hf eMeO Hf YHjO Hf SajGf Hf bjS, CHh HcQ, GHf CHj GdOfjG GdbQTj , J (B281 (3g` s ((3OeTb s)
(3ChdgG (B:s
(3CNHQfG GdTjN GdUGdM CHh HcQ eMeO Hf Ydi Hf eMeO GdNjGW GdebQi bGd (B: (3RQY QLd ef Cgd GdWGFa RQYkG adeG HdZ EUGHJg Cag s
(3BNQgG (B:s
(3HdZ Cgd GdQVG GdQVG bGd HGdeYQaI hGdMeO ddg QH GdYGdejf s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B2s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B118 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B131s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJUha hGdBOGH GdTQYjIs